The changes of chili leaf structure by Geminivirus infection - Taufik, Muhammad; HS, Gusnawaty; Hasan, Asmar; Botek, Muhammad; Firihu, Muhammad Zamrun; Variani, Viska Inda; Tihurua, Eka Fatmawati; Wulansari, Tri Yuni Indah (Universitas Lampung, 2024)
The Geminivirus in chili plants is a significant problem in chili cultivation. Symptoms of Geminivirus infection are quite easy to find in chili plants because the symptoms are quite typical: mosaic, yellowing, small leaves, leaf lamina malformation, and stunting. The visual changes in leaf morphology are due to the leaf tissue structure, such as the upper and lower epidermis and the mesophyll tissue, including the palisade and sponge. There is little information about changes in the structure of chili plants infected with the Geminivirus. Therefore, this study aims to add information about changes in the leaf tissue structure of chili plants infected with the Geminivirus. The structural changes observed were palisades. Long palisades were less preferred by whiteflies, so the incidence of geminivirus disease was lower. This information is a reference for assembling chili plants with better structural resistance. The method used was a cross-section of chili leaves, double staining, and observation with a light microscope. Observations on mild symptoms showed epidermal cells shrinking. Some parts of palisade leaves were composed of two layers with shortened cells and tend to be oval. The symptom is that the upper epidermal cells were shrunken, and the palisade also tends to shorten. Severe symptoms of the epidermis on the leaves were curly, shriveled, thinned, and even dying; the palisade is shortened and sometimes looks irregular/tight. Changes in the leaf tissue of chili plants infected with the Geminivirus cause changes at the ultra-structural, cell, or tissue level, depending on the type of virus attack and the attack level.